MENILAI KINERJA KEUANGAN PT BANK SYARIAH INDONESIA TBK DENGAN MENGGUNAKAN METODE COMMON SIZE (PERIODE 2021-2023) - Aulia, Donesta Nova; Arisandy, Yosy; Makmur (Jurnal Riset Terapan Akuntansi, 2025)
The purpose of this research is to evaluate PT Bank Syariah Indonesia Tbk's financial results from 2021 to 2023. PT Bank Syariah Indonesia Tbk's annual financial report for the years 2021–2023 served as both the population and the sample for this quantitative descriptive research. The common size approach is used to analyze the secondary data and determine the percentage of each item in comparison to the profit and loss report and balance sheet. According to the study's findings, the bank's financial performance is expected to remain steady in 2021. Liabilities fluctuated in 2022 despite a gain in numerous accounts, including cash and income. Even though a number of asset and liability accounts saw declines in 2023, the bank's earnings increased. Given the bank's capacity to sustain revenue growth over the course of the research, PT Bank Syariah Indonesia Tbk's financial performance may be deemed to be strong overall. This study can serve as a guide for strategic financial policy decisions in the Islamic banking industry and highlights the value of applying common size analysis when assessing financial structure. Keywords: Financial Performance, Common Size, Bank Syariah Indonesia (BSI)